2021
DOI: 10.1532/hsf.3621
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Atrial Fibrillation after Minimally Invasive Direct Coronary Artery Bypass: A Single-Center, 5-Year Follow-Up Study

Abstract: Objective: To evaluate the risk factors and explore the mid-term outcomes of postoperative atrial fibrillation (POAF) after minimally invasive direct coronary artery bypass (MIDCAB). Methods: A total of 165 patients, who underwent isolated MIDCAB from 2012 to 2015, were enrolled in the study and retrospectively reviewed. Patients with preoperative arrhythmia, concomitant surgical procedures were excluded. All patients were continuously monitored for POAF until discharge, and two groups were formed: the non-POA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…CABG surgery has the highest incidence for developing POAF and other long-term effects and methods to reduce the incidence of POAF in CABG patients has been the focus for many clinical trials. A follow-up study comparing minimally invasive direct coronary artery bypass (MIDCAB) showed no correlation to POAF [ 53 ]. Transcatheter Aortic Valve Replacement (TAVR) is a method that is increasing in popularity over Surgical Aortic Valve Replacement (SAVR), due to it being less invasive [ 1 , 54 ].…”
Section: Methodsmentioning
confidence: 99%
“…CABG surgery has the highest incidence for developing POAF and other long-term effects and methods to reduce the incidence of POAF in CABG patients has been the focus for many clinical trials. A follow-up study comparing minimally invasive direct coronary artery bypass (MIDCAB) showed no correlation to POAF [ 53 ]. Transcatheter Aortic Valve Replacement (TAVR) is a method that is increasing in popularity over Surgical Aortic Valve Replacement (SAVR), due to it being less invasive [ 1 , 54 ].…”
Section: Methodsmentioning
confidence: 99%
“…Among the 8974 identified (6212 screened) articles, a total of 59 studies published between 1993 and 2022 were included in the present analysis. 3 , 4 , 5 , 7 , 12 , 13 , 14 , 15 , 16 , 17 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , ...…”
Section: Resultsmentioning
confidence: 99%
“…As previously mentioned, VitD is one of the inhibitors of this axis, and its deficiencies may be associated with excessive atrial fibrosis and the formation of ectopic foci and re-entry loops. It has been documented that VitD supplementation inhibits the development of PoAF in some patients with excessive RAAS activation [ 87 , 88 ]. PoAF on the background of VitD deficiency is multifactorial, and there are many indications that it acts through IAF mechanisms, but it seems that the critical point is the level of VitD at the time of entering cardiac surgery, since such procedures induce high stress and mobilize the body to counteract human-induced changes.…”
Section: Pathogenesis Of Af and Role Of Vitd In Its Inductionmentioning
confidence: 99%